Potensi Cendawan Asal Hydrilla verticillata Sebagai Pengendali Hayati Fusarium oxysporum dan Ganoderma boninense: Fungi from Hydrilla verticillata as Potential Biological Control Agents of Fusarium oxysporum and Ganoderma boninense - Astri Ariyani; Nampiah Sukarno; Sri Listiyowati (Jurnal Sumberdaya Hayati, 2019)
Hydrilla verticillata is an aquatic weed, can build symbiosis and also become a substrate of freshwater fungi. Some of freshwater fungi that live in association with H. verticillata are pathogenic fungi which were potentially used as controller for Fusarium oxysporum and Ganoderma boninense. The use of pathogenic fungi as a biocontrol is not consistent in the field. Therefore, this research aimed to find new fungus candidates that are stronger and more consistent in controlling pathogenic fungi. Freshwater fungi were isolated from H. verticillata. Identification was based on morphological characters. Molecular analysis was carried out for freshwater fungi which had the highest inhibition percentage to pathogenic fungi. The antagonism test was conducted by dual culture method. The mechanism of interaction of hyphae was observed under a microscope. Freshwater fungi was derived from H. verticillata stem are Aspergillus section flavi, Gliomastix sp., and Talaromyces sp. Antagonism test results showed that all fungi could inhibit the growth of pathogenic fungi. Based on molecular analysis used ITS region showed Talaromyces sp. could not identify to the level of species so that additional genes were required, namely beta-tubulin gene, in order to further identify Talaromyces sp.